The Paradigm of Progressive Education in Theory and Practice of Muhammadiyah Organizational History - Hidayatullah, Taufik; Nurhakim, Moh. (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The purpose of this research is to explore how the paradigm of progressive education in theory and practice in the Muhammadiyah organization using historical methods with steps including heuristics, source criticism: internal and external, interpretation, and historiography. Based on the results of the study, it shows that the founder of the Muhammadiyah organization, K.H. Ahmad Dahlan, played an important role in this matter. His thoughts on Islam, life, and education became the foundation of a progressive education. However, it still strongly stays based on the Al-Quran and Al-Sunnah. The Muhammadiyah organization emphasizes its efforts to improve religious life with practices such as in the field of education. K.H. Ahmad Dahlan is also able to offer a new education model as a renewal of conventional education from Dutch schools and pesantren. Thus, Muhammadiyah’s education can give birth to a new generation that is more “kaffah.”